Optimal project organizational structure for construction management. - Min-Yuan Cheng (Journal of construction engineering and management)
This study on the trend model to investigate various modes of coordination among team members of construction projects. According to the project network developed based on the characteristics of a project, the trend model establishes an activity relationship matrix (ARM) to identify the activity relationships within the construction process. ARM is used to construct an organizational structure for project management and a communication resistance matrix that shows the efficiency of communication and coordination among the members of the project team. To evaluate various organizational structures and their coordination efficiencies, this study utilizes the analytical hierarchy process to quantify the strength of an organizational structure and identify the optimal structure for project management. Through quantitative modeling of communication efficiency among organizational team members, an objective function for calculating the total resistance index is used to determine the optimal organizational structure available to execute the project. This study demonstrate how the trend model may be applied in the future for evaluating the coordination efficiencies of various organizational structures.